Pembangunan Kakas Bantu Pengukuran Kopling Agregat pada Perangkat Lunak berbasis Objek - Fikar Mukamal; Fajar Pradana; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Coupling is a fundamental attribute of software which has a great influence on software quality. Couplings negatively affect the quality of the software. The higher the coupling value, the more difficult the changes to the software will be made. Changes to software during the life cycle are a certainty. Changes that are not implemented properly can cause damage and increase maintenance costs. So that software maintenance can be carried out efficiently, it is important for developers to keep the coupling values low. Various coupling metrics are proposed by the researchers, one of which is Aggregated Coupling Measure (ACE). ACE metrics combine structural and conceptual coupling metrics into aggregate coupling metrics so as to better identify couplings than separate measurements. However, there is no application that applies the ACE metric, so the calculation is still done manually which of course will take a lot of time and effort and is inefficient to apply to large and complex applications. Therefore, an aggregate coupling measurement tool was developed for Java-based software using the ACE metric. The tools have been verified from the unit level using the white-box strategy to the validation of the overall functionality using the black-box strategy. Testing the accuracy and performance of the system produces an accuracy value of 100% and an average of 385 times faster than manually counting.